2018
DOI: 10.5603/gp.a2018.0077
|View full text |Cite
|
Sign up to set email alerts
|

Skin changes during pregnancy. Is that an important issue for pregnant women?

Abstract: Self-reported skin complaints seem to be a relevant problem during pregnancy. Proper skin care as well as appropriate treatment applied by obstetricians and/or dermatologists may help women to recover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
1
10
0
4
Order By: Relevance
“…In our study, pregnant females with skin changes had significantly reduced quality of life compared to those without (p<0.001). Similar to our results, Ciechanowicz et al (18) , reported about 43.67% of women with dermatological problems during pregnancy showed significant deterioration in their wellbeing. Furthermore, Uyanikoglu and Aksoy (19) , in their study, showed a slight but statistically insignificant reduced quality of life in pregnant females with melasma (P>0.05).…”
Section: Resultssupporting
confidence: 93%
“…In our study, pregnant females with skin changes had significantly reduced quality of life compared to those without (p<0.001). Similar to our results, Ciechanowicz et al (18) , reported about 43.67% of women with dermatological problems during pregnancy showed significant deterioration in their wellbeing. Furthermore, Uyanikoglu and Aksoy (19) , in their study, showed a slight but statistically insignificant reduced quality of life in pregnant females with melasma (P>0.05).…”
Section: Resultssupporting
confidence: 93%
“…Therefore, we speculate that due to changes in ostrogen during pregnancy, there is a decrease in SSL secretion and weakening of the skin barrier. However, some epidemiological investigation 4 , 36 38 have found that acne is also a common condition during pregnancy. It is worth noting that acne occurs most often in the third trimester of pregnancy due to increased sebum secretion from maternal androgens, which does not contradict our results (the sampling population was women in the second trimester of pregnancy).…”
Section: Discussionmentioning
confidence: 99%
“…psoriasis, and atopic dermatitis [AD]), may worsen or improve during pregnancy, and pregnancy-specific skin diseases, such as intrahepatic cholestasis and pruritic urticarial papules, may occur 3 . Skin diseases during pregnancy have received extensive attention and research 4 , 5 and often occur in close association with, changes in skin condition 6 . Therefore, we speculated that the state of the skin changes and is prone to some skin diseases during pregnancy, but at the molecular level, the specific changes that take place remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly encountered physiological changes during pregnancy are pigmentary alterations, the most common colouration being melasma, linea nigra, palmar erythema (Ciechanowicz et al, 2018;Urasaki, 2010). Many factors have associated with the development of pigmentation, including hormonal influences of pregnancy, like elevated ACTH levels, estrogen and progesterone, ultraviolet radiation.…”
Section: Discussion 41pigmentation During Pregnancymentioning
confidence: 99%